2007
DOI: 10.1038/nrmicro1750
|View full text |Cite
|
Sign up to set email alerts
|

Marine viruses — major players in the global ecosystem

Abstract: Viruses are by far the most abundant 'lifeforms' in the oceans and are the reservoir of most of the genetic diversity in the sea. The estimated 10(30) viruses in the ocean, if stretched end to end, would span farther than the nearest 60 galaxies. Every second, approximately 10(23) viral infections occur in the ocean. These infections are a major source of mortality, and cause disease in a range of organisms, from shrimp to whales. As a result, viruses influence the composition of marine communities and are a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

36
2,135
1
43

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 2,589 publications
(2,307 citation statements)
references
References 163 publications
36
2,135
1
43
Order By: Relevance
“…Viruses are increasingly considered as part of efforts to understand the factors controlling marine microbial mortality, productivity, and biogeochemical cycles [8,9,19,39,45,55]. Quantitative estimates of these viralinduced effects can be measured directly, but are often inferred indirectly, using the relative abundance of viruses to prokaryotes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Viruses are increasingly considered as part of efforts to understand the factors controlling marine microbial mortality, productivity, and biogeochemical cycles [8,9,19,39,45,55]. Quantitative estimates of these viralinduced effects can be measured directly, but are often inferred indirectly, using the relative abundance of viruses to prokaryotes.…”
Section: Discussionmentioning
confidence: 99%
“…The minimal predictive value of prokaryoate abundances in the near-surface when aggregating across all surveys is problematic given that virus-microbe interactions have significant roles in driving prokaryote mortality and ecosystem functioning [9,45,53]. Indeed the aggregation of abundance measurements in terms of total prokaryote abundances may represent part of the problem.…”
Section: Discussionmentioning
confidence: 99%
“…The recent discovery of viral abundance and diversity of natural environment caused a huge interest to viral ecology [10,[21][22][23]. Allochthonous and autochthonous viruses have a crucial influence on the microbial ecosystem.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the interrelation of respective phages and bacteria makes up the same balance as the ratio of predators and rodents in the macrocosm. Viruses are responsible for 20-40% of marine microbial mortality [23]. Viral-induced lysis of microbes redirects organic matter back into the microbial loop and away from microalgae, zooplankton Comparative study of viromes from freshwater samples of the Ile-Balkhash region of Kazakhstan… 21 and fish [4,24].…”
Section: Discussionmentioning
confidence: 99%
“…2014). In the ocean, viruses are by far the most abundant biological entity and behind prokaryotes constitute the second largest pool of biomass (Suttle 2007). Viruses are obligate parasites and lack the ability for active movement making finding the right host organism a stochastic process that is abundance‐dependent (Murray and Jackson 1992).…”
Section: Introductionmentioning
confidence: 99%